The Evolution of GEOINT-Cyber Integration in Modern Warfare: A Systematic Review of Operational Paradigms, Enabling Technologies, and Implementation Challenges - Ryan Sabian; Sukendra Martha; Yosef Prihanto (International Journal of Technology and Education Research, 2026)
In an era of converging digital and physical realities, the integration of Geospatial Intelligence (GEOINT) and cyber operations has become a strategic imperative for modern defense. This systematic review examines the evolution of GEOINT-cyber integration from 2016 to 2025, synthesizing operational paradigms, enabling technologies, and implementation challenges. Methodologically, the study adopts a Systematic Literature Review (SLR) following the PRISMA 2020 framework. Data were collected using Publish or Perish (PoP) from Crossref and Google Scholar, with keywords including “cyber warfare” and “GEOINT.” From an initial pool of 216 articles obtained, only 4 articles met the inclusion criteria for the analysis stage. Key findings highlight three pivotal developments: (1) the Internet of Things (IoT) serves as both a distributed GEOINT sensor network and a cyberattack vector; (2) epidemiological models provide an analytical framework for tracking cyber threats across spatial and cognitive domains; and (3) Cognitive Intelligence (COGINT) enables the geospatial mapping and influence of human decision-making. Case studies such as the Ukraine conflict and Operation “Salt Typhoon” illustrate real-world applications while revealing tensions between security efficacy, ethical governance, and human dignity. The study concludes that the future of GEOINT-cyber integration will be shaped not only by technological advances but also by principled frameworks that balance operational effectiveness with societal values. This review offers a structured, human-centric overview of a rapidly evolving domain, contributing to both academic discourse and professional practice.